INSTILLING CHARACTER THROUGH THE MODEL OF BUILDING RELIGIOUS AND VALUE BASED EDUCATION (BRAVE): HONESTY, COURAGE, INDEPENDENCE - Koko Khoerudin; Aan Hasanah; Qiqi Yuliati Zaqiah; Teti Ratnasih (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to create character education innovation through the development of the BRAVE (Building Religious and Value-based Education) Model. The primary focus of this innovation is to integrate religious values—honesty, courage, and independence—into a digital educational game platform to address the lack of adaptive character-learning media for early childhood in the digital age.Methodology – This research uses the Research and Development (R&D) method with a 4-D procedure (Define, Design, Develop, Disseminate). The Define stage included an analysis of the needs of teachers at Raudhatul Athfal (RA) institutions; the Design stage produced a prototype of an interactive digital game based on moral dilemma scenarios; and the Develop stage involved validation by six experts (in materials, media, and practitioners) with a feasibility score of 89%. The model was tested on a limited basis with 60 students at four partner RAs.Findings – The study's results confirm that digital educational games in the BRAVE Model significantly transform children's behavior. Pretest-posttest analysis shows a dramatic increase in honesty (58% to 84%), courage (55% to 81%), and independence (60% to 86%), with p < 0.05. Qualitative findings reveal that the game's interactivity increases children's emotional involvement, enabling the internalization of religious values to occur more naturally and permanently than with conventional methods.Contribution – The BRAVE model has proven to be an innovative and applicable solution for early childhood education institutions seeking to strengthen religious character through the measured, systematic use of digital media.